The Impact of Lerep Tourism Village Development on Tourism Businesses - Syaiful, Ahmad (Universitas Negeri Semarang, 2021)
The purpose of this study is to identify the condition of the Lerep Tourism Village before and after the development of the tourism village and the impact of the development of the Lerep Tourism Village on the economy of tourism businesses. Data collection techniques using purposive sampling technique. The sample in this study were 98 respondents who had businesses or services in the tourism sector. Data analysis method is statistical descriptive analysis. The results of research are known to have an impact on improving the conditions of attraction, accessibility, amenities, ancillary, and social culture of the community. The development of Lerep Tourism Village also had an impact on the economy of tourism businesses in Lerep Village. With the development of a tourism village, it can increase the income of business operators and tourism services to IDR 450,000 per month. The income of business operators and tourism services can increase up to three times when there are many tourists visiting. The existence of Lerep Tourism Village opens new job opportunities for the community such as selling souvenirs, accessories, lodging businesses, and performing arts workers. Tujuan dari penelitian ini adalah mengidentifikasi kondisi Desa Wisata Lerep sebelum dan sesudah pengembangan desa wisata serta mengidentifikasi dampak pengembangan Desa Wisata Lerep terhadap perekonomian pelaku usaha pariwisata. Teknik pengumpulan data menggunakan teknik purposive sampling. Sampel pada penelitian ini adalah 98 responden yang memiliki usaha atau jasa di sektor pariwisata. Metode analisis data adalah analisis deskriptif statistik. Hasil penelitian diketahui memberikan dampak peningkatan kondisi atraksi, aksesibilitas, amenitas, ancillary, dan sosial budaya masyarakat. Pengembangan Desa Wisata Lerep juga memberikan dampak pada perekonomian pelaku usaha pariwisata di Desa Lerep. Dengan pengembangan desa wisata, dapat meningkatkan pendapatan pelaku usaha dan jasa pariwisata hingga Rp 450.000 per bulan. Pendapatan pelaku usaha dan jasa pariwisata bisa meningkat sampai tiga kali lipat pada saat ramai kunjungan wisatawan. Keberadaan Desa Wisata Lerep membuka peluang kerja baru bagi masyarakat seperti menjual cinderamata, aksesoris, usaha penginapan, dan pekerja seni pertunjukan.